Factors associated with carotid artery calcification in the general working-age population - V. S. Kaveshnikov; I. A. Trubacheva; M. A. Kuzmichkina; V. Kh. Vaizov (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study factors associated with carotid artery calcification as an atherosclerotic marker in the general working-age population.Material and methods. The data of a representative ESSE-RF sample aged 25-64 years (n=1412) were studied. They underwent standard cardiology screening and assessment of carotid plaque (CP) characteristics using ultrasound. All respondents signed an informed consent to participate in the study. The association analysis included socio-demographic, anamnestic, laboratory, and ultrasound characteristics. Univariate and multivariate statistics were used.Results. The prevalence of detection of calcified CP (cCP) was 5,4% — 7,8% in men and 3,7% in women (odds ratio (OR)=2,2; p=0,001). The probability of cCP detection was associated with following factors: male sex (OR=3,9; p<0,001), age (OR=1,2; p<0,001), total cholesterol (women, OR=1,7; p=0,001), history of thyrotoxicosis (OR=2,1; p=0,034), osteoporosis (OR=2,6; p=0,009), and smoking (OR=1,8; p=0,046). The odds that the detected plaque would be calcified were higher in individuals in the 4th quartile of mean plaque size distribution (OR=3,8; p<0,001) and in the presence of the following factors: male sex (OR=1,9; p=0,031), age ≥55 years (OR=4,3; p<0,001), osteoporosis (OR=3,2; p=0,007), high-density lipoprotein cholesterol level ≥1,3 mmol/l (OR=2,0; p=0,025).Conclusion. The obtained data indicate an association of carotid calcification with both traditional cardiovascular risk factors and systemic diseases associated with impaired calcium and phosphorus metabolism (thyrotoxicosis, osteoporosis). The study results can be useful in practical healthcare, research, and developing preventive technologies.